2008
DOI: 10.1007/s10695-008-9288-0
|View full text |Cite
|
Sign up to set email alerts
|

Classification accuracy of algorithms for blood chemistry data for three aquaculture-affected marine fish species

Abstract: The objective of this study was determination and discrimination of biochemical data among three aquaculture-affected marine fish species (sea bass, Dicentrarchus labrax; sea bream, Sparus aurata L., and mullet, Mugil spp.) based on machine-learning methods. The approach relying on machine-learning methods gives more usable classification solutions and provides better insight into the collected data. So far, these new methods have been applied to the problem of discrimination of blood chemistry data with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…On the contrary, Coz-Rakovac et al (2008) found no correlation between TP values and the fish feeding regime. The observed lower TP values in well fed O. melanura around cages are similar to those estimated for the aquaculture-affected sea bream (Coz-Rakovac et al, 2009), but any conclusions that are not supported by significant results would be very speculative. Moreover, although a difference in plasma CHOL between sampled populations was observed, its significance could not be determined due to the strong departure from normality of even log-transformed values.…”
Section: Accepted Manuscriptsupporting
confidence: 63%
See 2 more Smart Citations
“…On the contrary, Coz-Rakovac et al (2008) found no correlation between TP values and the fish feeding regime. The observed lower TP values in well fed O. melanura around cages are similar to those estimated for the aquaculture-affected sea bream (Coz-Rakovac et al, 2009), but any conclusions that are not supported by significant results would be very speculative. Moreover, although a difference in plasma CHOL between sampled populations was observed, its significance could not be determined due to the strong departure from normality of even log-transformed values.…”
Section: Accepted Manuscriptsupporting
confidence: 63%
“…However, we can just point out that observed GLU values of both saddled bream populations were lower than those estimated for the aquaculture-affected sea bream (Coz-Rakovac et al, 2009). The levels of TRIG are considered to be major indices of the health status of teleost, but they are not a reliable indicator of fish nutritional status (Wagner and Congleton, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 78%
See 1 more Smart Citation
“…For instance, Coz-Rakovac et al [100] identified three aquaculture-affected species such as 120 seabass (Dicentrarchus labrax), 98 sea bream (Sparus aurata L.), and 66 mullets (Mugil spp.) thanks to biochemical data using machine learning methods.…”
Section: Classification and Identificationmentioning
confidence: 99%
“…There are 3 species which are identified based on their biochemical traits. The methodology of this study is shown in Figure 30 with decision tree and biochemistry analysis (AST, TP, TRIG, CHOL, and GLU collected from blood) [100].…”
Section: Classification and Identificationmentioning
confidence: 99%